Comparison of Biparametric and Multiparametric MRI for Clinically Significant Prostate Cancer Detection With PI‐RADS Version 2.1. Issue 1 (2nd July 2020) - Tamada, Tsutomu; Kido, Ayumu; Yamamoto, Akira; Takeuchi, Mitsuru; Miyaji, Yoshiyuki; Moriya, Takuya; Sone, Teruki
Abstract : Background: Biparametric MRI (bpMRI) without dynamic contrast‐enhanced MRI (DCE‐MRI) results in an elimination of adverse events, shortened examination time, and reduced costs, compared to multiparametric MRI (mpMRI). The ability of bpMRI to detect clinically significant prostate cancer (csPC) with the Prostate Imaging and Reporting Data System version 2.1 (PI‐RADS v2.1) compared to standard mpMRI has not been studied extensively. Purpose: To compare the interobserver reliability and diagnostic performance for detecting csPC of bpMRI and mpMRI using PI‐RADS v2.1. Study Type: Retrospective. Population: In all, 103 patients with elevated prostate‐specific antigen (PSA) levels who underwent mpMRI and subsequent MRI‐ultrasonography fusion‐guided prostate‐targeted biopsy (MRGB) with or without prostatectomy. Field Strength/Sequences: T2 ‐weighted imaging (T2 WI), diffusion‐weighted imaging (DWI), and DCE‐MRI at 3T. Assessment: Three readers independently assessed each suspected PC lesion, assigning a score of 1–5 for T2 WI, a score of 1–5 for DWI, and positive and negative for DCE‐MRI according to PI‐RADS v2.1 and determined the overall PI‐RADS assessment category of bpMRI (T2 WI and DWI) and mpMRI (T2 WI, DWI, and DCE‐MRI). The reference standard was MRGB or prostatectomy‐derived histopathology. Statistical Testing: Statistical analysis was performed using the kappa statistic and McNemar and Delong tests. Results: Of the 165 suspected PC lesions in 103 patients, 81 were diagnosed with csPC and 84 with benign conditions. Interobserver variability of PI‐RADS assessment category showed good agreement for bpMRI (kappa value = 0.642) and mpMRI (kappa value = 0.644). For three readers, the diagnostic sensitivity was significantly higher for mpMRI than for bpMRI ( P  < 0.001 to P = 0.016, respectively), whereas diagnostic specificity was significantly higher for bpMRI than for mpMRI ( P  < 0.001 each). For three readers, the area under the receiver operating characteristic curve (AUC) was higher for bpMRI than for mpMRI; however, the difference was significant only for Reader 1 and Reader 3 (Reader 1: 0.823 vs. 0.785, P = 0.035; Reader 2: 0.852 vs. 0.829, P = 0.099; and Reader 3: 0.828 vs. 0.773, P = 0.002). Data Conclusion: For detecting csPC using PI‐RADS v2.1, the interobserver reliability and diagnostic performance of bpMRI was comparable with those of mpMRI. Level of Evidence: 4 Technical Efficacy Stage: 2